Gentrification As A Politico‐Economic Window: Reflections On The Changing State Of Gentrification. (12th October 2018) - Hackworth, Jason
Abstract: This essay provides some reflections on the 'Changing State of Gentrification' article published in 2001. I focus on three areas that have been raised as critiques of this article: (i) the issue of generalisability; (ii) the mechanics of 'waves'; and (iii) the conceptualisation of the state. I reemphasise the importance of using gentrification as a window to wider politico‐economic change.